1997
DOI: 10.2307/3579484
|View full text |Cite
|
Sign up to set email alerts
|

Radium Dial Workers: Issues concerning Dose Response and Modeling

Abstract: The mortality pattern of women who began employment as luminizers in the radium dial industry before 1930 was followed through 1990. Hazard models with time-dependent covariates were used on mortality data either organized by individual death times or grouped into cross-classified person-year tables. These models were used to quantify trends in mortality associated with either death from or diagnosis of bone sarcoma or head carcinoma. The accumulation of skeletal doses from 226Ra and 225Ra was an important pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 17 publications
0
13
0
3
Order By: Relevance
“…Studies on painters of luminous dials contaminated with 226 Ra and 228 Ra in the past revealed an excess in osteosarcomas but not at doses Ͻ10 Gy (Carnes et al 1997). Also, in patients receiving thorotrast (thorium based), a threshold of about 2 Gy was observed for hepatomas (Travis et al 2003).…”
Section: Epidemiological Surveysmentioning
confidence: 97%
“…Studies on painters of luminous dials contaminated with 226 Ra and 228 Ra in the past revealed an excess in osteosarcomas but not at doses Ͻ10 Gy (Carnes et al 1997). Also, in patients receiving thorotrast (thorium based), a threshold of about 2 Gy was observed for hepatomas (Travis et al 2003).…”
Section: Epidemiological Surveysmentioning
confidence: 97%
“…Recent studies have also addressed other aspects of radiation poisoning among U.S. radium dial workers. Carnes, et al (1997) adopted Cox's (1972) hazard regression to build a dose response model. Although they incorporated AFE, a time-related confounding factor, into their model, the AFE was shown to be insignificant according the Poisson model used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Pour des doses supé rieures à quelques grays, la fré quence des cancers induits croît brutalement, sans doute parce que la proportion de cellules lé sé es devient plus grande. Ce seuil est manifeste pour les osté osarcomes observé s chez les peintres en cadran lumineux contaminé s par la peinture au radium [43] et les cancers du foie observé s chez les malades à qui l'on a injecté du thorotrast (qui contient du thorium) comme produit de contraste [222]. La dose par cellule varie peu (c'est celle administré e lors de la traversé e d'une cellule par une particule a), ce qui varie avec la dose est la proportion de cellules où survient l'é mission d'une particule par unité de temps.…”
Section: Mé Canismes Tissulaires De Dé Fense : Le Micro-environnementunclassified